Funcionarios Centro de Investigación Académica. (UNED, 2025)
En el orden usual: Benicio Gutiérrez, Roy Umaña, Giuseppa D'Agostino, Cristina D'Alton, Rodrigo Alfaro, Alexandra Abarca, Ana María Rodino, Elisa Delgado y Alejandra Cruz